A study on the content of integrity policies and research integrity management in Chinese universities - Yuan Cao; Yuwei Jiang; Yong Zhao (Frontiers in Research Metrics and Analytics, 2023)
BackgroundThis study outlines a comprehensive analysis of the primary characteristics of managing research integrity (RI) in domestic colleges and universities in China. RI education in China consists primarily of soft advocacy, with no hard requirements or continuous and systematic support. Together with other stakeholders, such as funders and publishers, higher education institutions (e.g., colleges and universities) are one of the vital actors that have a lot of influence on RI promotion and implementation among researchers. However, the literature on the regulation of RI policies in China's universities is limited.MethodsWe investigate the top 50 colleges and universities in the 2021 Best Chinese Universities Ranking. Their guidance and policy documents on RI were collected via their official websites. By integrating the use of scientometrics analysis, including descriptive statistical analysis, inductive content analysis, and quantitative analysis, we examine whether and how these higher education institutions respond to national policies in a timely manner, especially in terms of their frequency of updates, topic clustering analysis, terms clustering analysis, content aggregation. To further understand the composition mechanism and the main working systems of university RI management organizations, we conducted in-depth research on the organizational functions, meeting system, staff composition mechanism, and scientific research misconduct acceptance and investigation mechanisms.ResultsThe regulations on the treatment of RI in China's universities have, in response to the government's call to establish their own management policies and working mechanisms, maintained a zero-tolerance stance on research misconduct. The sampled universities listed the definition and principles of misconduct practices, investigation procedures, and sanctions of research misconduct in their own policy documents. Some of them listed inappropriate research practices All 50 sampled universities have formed relevant organizations responsible for RI management, they all provide the detailed regulations of the committees. Yet, there is still a need to further define Questionable Research Practice, foster higher standards for integrity in research and, establish and improve an efficient, authoritative, well-restrained and supervision working mechanism for organizations responsible for RI treatment.